We are the games: The COVID-19 pandemic and athletes` voices; Somos los juegos: la pandemia de la COVID-19 y las voces de los/as atletas - Donnelly, P. (Sociología del Deporte, 2020)
On Sunday evening, March 22, 2020, the Canadian Olympic Committee (COC) and the Canadian Paralympic Committee (CPC) announced that Canadian athletes would not attend the Tokyo 2020 Olympics and Paralympics unless they were postponed. On Tuesday, March 24, 2020, the International Olympic Committee (IOC) announced that the Tokyo 2020 Olympics would be postponed for one year. This paper begins by describing the strong part played by athletes in Canada`s decision, and the IOC`s decision to postpone the Olympics; continues with a brief examination of the suppression of athlete voices, and their renewed growth in recent years; and concludes with some thoughts on the potential for athletes to continue, given the circumstances created by the COVID-19 pandemic, their increasingly successful struggle against the culture of control that is modern high performance and professional sport.